2019
DOI: 10.7150/jca.27753
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Postsurgical Adjuvant Therapy in Patients with Gastric Cancer: A Propensity Score Matching Study

Abstract: Background:In clinical trials, adjuvant therapy (AT) has been shown to improve the prognosis in patients with gastric adenocarcinoma who undergo curative gastrectomy and adequate lymph node dissection. However, the optimal timing for initiating AT is still unclear.Method:We collected data from 538 patients with stage II-III gastric cancer who underwent curative gastrectomy and AT in two tertiary hospitals from 2006 to 2013. Patients were divided into the early group (≤8 weeks, n=393) and the late group (>8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A logistic regression model was chose for calculating the propensity scores and the following covariates: tumor size, tumor location and tumor stage. The 1:1 matching process was peformed by using the nearest neighbor matching method, under a 0.2 caliper [28]. The optimal cutoff point of the ACCI was obtained through X-tile (Version 3.6.1, Yale University) [29, 30].…”
Section: Methodsmentioning
confidence: 99%
“…A logistic regression model was chose for calculating the propensity scores and the following covariates: tumor size, tumor location and tumor stage. The 1:1 matching process was peformed by using the nearest neighbor matching method, under a 0.2 caliper [28]. The optimal cutoff point of the ACCI was obtained through X-tile (Version 3.6.1, Yale University) [29, 30].…”
Section: Methodsmentioning
confidence: 99%
“…8,9 While many studies have examined the survival outcomes in POC patients with delayed TAC, the findings are inconsistent. [10][11][12] On the other hand, there have been a few studies of PEC outcomes with delayed TAC. 13 Moreover, little is known about the "flexion point" in the duration of chemotherapy; that is, the time frame in which optimal treatment efficacy can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other reports showed no survival benefit for patients who received AC within 4 weeks of surgery ( 23 ). A study in Taiwan showed that starting AC within 8 weeks of a gastrectomy resulted in an improved 5-year recurrent-free survival rate, possibly contributing to an improved OS ( 24 ). Another study on AC using S-1 chemotherapy, from Japan, found that the timing of AC was not associated with OS ( 25 ).…”
Section: Discussionmentioning
confidence: 99%